Pengaruh Indeks Pembangunan Manusia, Pertumbuhan Ekonomi, Rumah Layak Huni, Fasilitas Kesehatan Dan Pernikahan Dini Terhadap Prevalensi Stunting di Indonesia - Intihatun Munawaroh; Abdul Aziz Ahmad (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Efforts to address stunting have been carried out by the Indonesian government from the central to the regional levels, but the results have not met the targets set by the SDGs and national targets. This study aims to analyze the factors that cause stunting and to determine which factors are the most dominant in influencing stunting in Indonesia. This study uses a quantitative approach by applying the panel data multiple linear regression method. The data used in this study are secondary data sourced from BPS in the form of stunting prevalence data, Human Development Index, economic growth, livable housing, health facilities and early marriage from 2015 - 2023 in 34 provinces in Indonesia. The results of this study indicate that the HDI variable has a significant negative effect on the prevalence of stunting. The economic growth variable does not affect the prevalence of stunting. The livable housing variable does not affect the prevalence of stunting. The health facility variable has a significant negative effect on the prevalence of stunting. The early marriage variable has a significant positive effect on the prevalence of stunting. The findings of this study imply that 1) the government needs to take action to improve the quality of human resources through the dimensions of health, education and decent living standards 2) that economic growth does not affect the decline in stunting because there are other factors that have a greater influence on the prevalence of stunting 3) The government in collaboration with the community and institutions evaluates and controls budget provision activities for decent housing so that they are appropriate and on target 4) The government in collaboration with the community and institutions really needs to increase the availability of health facilities and health workers starting from integrated health posts, health centers to hospitals 5) the government really needs to increase socialization to the community through schools to provide education to adolescents about the many risks that arise in early marriage that can cause stunting in toddlers.